2003
DOI: 10.1115/1.1629752
|View full text |Cite
|
Sign up to set email alerts
|

Wind Shear and Turbulence Effects on Rotor Fatigue and Loads Control

Abstract: The effects of wind shear and turbulence on rotor fatigue and loads control are explored for a large horizontal axis wind turbine in variable speed operation at wind speeds from 4 to 20 m/s. Two- and three-blade rigid rotors are considered over a range of wind shear exponents up to 1.25 and a range of turbulence intensities up to 17%. RMS blade root flatwise moments are predicted to be very substantially increased at higher wind shear, and resultant fatigue damage is increased by many orders of magnitude. Smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 2 publications
1
34
0
Order By: Relevance
“…To answer this question, we use published results based on standardized simulation methods. Eggers et al . used the YawDyn/Aerodyn code to analyze loads from wind shear on a turbine with an 84 m hub height and a 35 m rotor radius ( R * = 0.417).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To answer this question, we use published results based on standardized simulation methods. Eggers et al . used the YawDyn/Aerodyn code to analyze loads from wind shear on a turbine with an 84 m hub height and a 35 m rotor radius ( R * = 0.417).…”
Section: Resultsmentioning
confidence: 99%
“…Although the dimensionless moment is only a function of R * and m , the actual moment depends on the design attributes specific to the turbine. According to Eggers et al ., this system produces P = 1.5 MW at 12 m s −1 . Using these data with momentum theory, P=2ρAVh3a1a2, gives an effective axial induction factor of a = 0.118 (for this system at this speed); the corresponding nominal thrust is F0=2ρAVh2a()1a=1410.24emnormalknormalN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While LLJs often greatly increase the speed of the wind in the rotor layer of a turbine (40-120 m above the ground in this study), shear and veer place additional stresses on the structure that can increase the need for regular maintenance and the possibility of mechanical failure (Eggers et al 2003;Kelley 2011). Correlation of wind speeds over large distances can also cause problems for balancing supply and demand on the energy grid if large amounts of wind-generated electricity dominate the system.…”
Section: Introductionmentioning
confidence: 89%
“…The wind shear and turbulence effects on rotor fatigue loads were studied by Eggers et al . The wind profile is modelled using the power law and turbulence using the von Kármán isotropic spectral tensor. They concluded that the increase in wind shear and turbulence increased rotor fatigue loads considerably.…”
Section: Introductionmentioning
confidence: 99%